2015
DOI: 10.1590/s0100-204x2015001200001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rue extract and its potential for controlling rice blast

Abstract: -The objective of this work was to purify and standardize the rue (Ruta graveolens) extract and evaluate its effect on Magnaporthe oryzae as an alternative to the integrated management of rice blast. The drug was characterized, the liquid extract was obtained, and the methodology for quantifying the standard markers psoralen and bergapten was validated. Rue extract and the markers, solely or in combination, were assayed in vitro, as well as in greenhouse conditions, for their ability to suppress leaf blast, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Plant extract of rue (Ruta graveolens) has potentiality to suppress rice blast in vitro, as well as in greenhouse conditions without damaging cell wall and plasma membrane of the fungus [40]. Rajeswari and Mariappan tested eleven plant extract and reported that Prosophis juliflora, Adhatoda vasica and Vitex negun restricted the radial growth of P. oryzae amended in apple agar medium [41].…”
Section: Discussionmentioning
confidence: 99%
“…Plant extract of rue (Ruta graveolens) has potentiality to suppress rice blast in vitro, as well as in greenhouse conditions without damaging cell wall and plasma membrane of the fungus [40]. Rajeswari and Mariappan tested eleven plant extract and reported that Prosophis juliflora, Adhatoda vasica and Vitex negun restricted the radial growth of P. oryzae amended in apple agar medium [41].…”
Section: Discussionmentioning
confidence: 99%
“…A espécie Ruta graveolens L. (R. graveolens) é uma planta que pertence à família Rutaceae e tem sido objeto de estudo por diversos pesquisadores devido ao seu efeito antifúngico. Popularmente a R. graveolens é conhecida como arruda, se caracterizando por ser um arbusto pequeno, de origem Mediterrânea, existente em todo o mundo (Reis et al, 2015).…”
Section: Arruda (Ruta Graveolens)unclassified
“…e plants were "rue" (Ruta graveolens L.), "horsetail" (Equisetum arvense L.), and "rosemary" (Rosmarinus officinalis L.). e plants selected for enrichment have medicinal properties and generate BM [54][55][56][57][58]. e activation procedure is as suggested by Dr. Teruo Higa [53] prior to definitive field application.…”
Section: Generation Inoculation and Characterization Of Beneficial Microorganisms In The Evaluation Stagementioning
confidence: 99%